Droplet-based PCR in a 3D-printed microfluidic chip for miRNA-21 detection. Issue 26 (19th June 2019) - Jiao, Zhiqiang; Zhao, Lei; Tang, Chu; Shi, Hongyan; Wang, Fu; Hu, Bo
Abstract : Droplet-based PCR detection of miRNA-21 was achieved using a 3D-printed microfluidic chip. Abstract : Recently, 3D printing technology has been widely applied in microfluidics due to its capacity of three-dimensional construction, rapid and automatic fabrication, and less time consumption. However, a droplet-based PCR in 3D-printed microfluidic chips is rarely reported. In this study, a 3D-printed microfluidic chip was designed and fabricated for droplet-based PCR detection of miRNA-21. In this chip, the capacity of monodisperse droplet generation was demonstrated. Moreover, the temperature of the chip was uniform and sufficiently stable, meeting the requirement for the PCR process. In addition, the working conditions of the droplet-based PCR process in the 3D-printed chip were explored. Finally, the droplet-based PCR detection of miRNA-21 levels in the MCF-10A cells and MDA-MB-231 cells was successfully achieved using the 3D-printed chip. We expect that the enormous potential of 3D printing technology in the research area of microfluidics will be explored in the future.